Concurrent hemorrhage and thrombosis: a case report of hemoptysis from pulmonary vein stenosis with left ventricular thrombus - Chen, Yingjie; Yu, Wei; Liu, Min; Liu, Qunxiang; Qin, Wei; Zhu, Ziyang; Chen, Shi; Li, Chenghong; Li, Fajiu (Frontiers in Cardiovascular Medicine, 2025)
We report a rare case of concurrent pulmonary vein stenosis (PVS) and left ventricular thrombus (LVT) in a 46-year-old male with dilated cardiomyopathy and prior radiofrequency catheter ablation for atrial fibrillation, who presented with hemoptysis and dyspnea. Imaging confirmed left pulmonary vein occlusion and LVT, creating a therapeutic conflict between bleeding control and anticoagulation. We implemented a staged strategy: urgent balloon angioplasty and large-diameter bare-metal stent implantation to improve PVS hemodynamics and halt hemoptysis; subsequently, rivaroxaban and clopidogrel were initiated for LVT. At 6-month follow-up, symptoms resolved with complete LVT absorption, though LIPV developed in-stent re-occlusion. This demonstrated that prioritizing PVS intervention before anticoagulation effectively balances hemorrhage and thrombosis risks in this complex scenario.